STUDY ETHNOMATHEMATICS: MENGUNGKAP KONSEP-KONSEP MATEMATIKA PADA ATURAN ADAT DALAM AKTIVITAS PEMBANGUNAN RUMAH TRADISIONAL MASYARAKAT ADAT KAMPUNG KUTA, KABUPATEN CIAMIS, JAWA BARAT - Putrietis, Malinda (2014)
Penelitianiniadalahupayauntukmenunjukkanketerkaitanantaramatematikadanbudaya.Selamainimatematikadianggaptidakadakaitannyasamasekalidenganbudaya (cultural free). Anggapantersebutberkembangakibatadanyakolonialismedalampendidikanmatematika.Hal tersebutsecaratidaklangsungmempengaruhiperkembanganmatematikadanpendidikanmatematika di beberapanegara.Sebagaiupayauntukmengatasihaltersebut, paramatematikawandanahlipendidikanmatematikainternasionalberkumpuldalamsuatukonferensimerumuskansuatu program yang dinamakanethnomathematcal program dan yang kemudiandikenalsebagaiethnomathematics. Penelitianinidilakukan di sebuahKampungAdat di KabupatenCiamis, Jawa Barat, yaituKampungKuta.Fokussituasisosial yang ditelitiadalahaturanadatdalamaktivitaspembangunanrumahtradisionalmasyarakatadatKampungKuta.Tujuannyayaituuntukmengungkapkonsep-konsepmatematikapadaaturanadatdalamaktivitaspembangunanrumahtradisionalMasyarakatadatKampungKuta.Penelitianinimenggunakanpendekatankualitatifdenganmetode ethnography.Hasiltemuandalampenelitianinidiungkapdenganmenggunakanmatematikadanbudayasebagaikerangkaacuan.Penelitianinimemberikanrekomendasikepadamasyarakatuntukmemandangbahwamatematikamemilikiketerkaitandenganbudaya. This research is an effort to show the relationship between mathematics and culture. During this time, mathematics has been viewed as cultural free. This view has been growing due to the colonialism in mathematics education. And it affects to the development of mathematics and mathematics education indirectly. An attempt to overcome this problem, mathematicians, mathematics educators and education policy makers held an international conference to discuss about a program, called ethnomathematical program, which had been the way of ethnomathematics. This research was done in a traditional village in KabupatenCiamis, Jawa Barat, ieKampungKuta. Focus situation which is studied in this research is the traditional rule of traditional building construction of indigenous people in KampungKuta. The aim of this research is to reveal mathematics concepts in the traditional rule of traditional building construction of indigeneous people in KampungKuta. This research use qualitative methods and ethnography. The result of this research is described within mathematics and culture as a term of reference. This research provide recommendations to the public to perceive that mathematics has a cultural significance.